Needs Analysis for Practical Guide Based Augmented Reality (AR) in an Effort to Support Basic Physics Practicum Activities During the Covid-19 Pandemic - Henny Johan; Desy Hanisa Putri; Eko Risdianto; Andik Purwanto; Septi Johan; Sipriyadi Sipriyadi (Universitas Lambung Mangkurat, 2023)
This study aims to conduct a field study on the need to develop Augmented Reality (AR) assisted practicum guidelines. Data collection instruments were in the form of questionnaires and interview guidelines. The subjects in this field study were students who became practicum assistants, physics laboratory staff, and lecturers of basic physics courses. Questionnaire data and interview results were analyzed qualitatively to see the real conditions of the practicum. Based on the results of data analysis, it is known that practicum manuals are still dominant in text, and practicum activities can be directed to practice problem-solving skills. The phenomenon of coastal areas can also be associated with physics practicum material. Based on the results of the practicum assistant's questionnaire, it is known that AR can facilitate physics practicum, so it is necessary to develop an AR-assisted practicum guide that presents audio-visual presentations. Based on the results of the interviews, it is also known that the constraints on practicum activities during this pandemic were that not all practicum courses were available at PheT to carry out virtual practicums, counter-dependence with assistant explanations in carrying out practicum procedures, so strict procedures could not be carried out, so it could be interpreted that a solution was needed an alternative practicum guide that is equipped with a video tutorial about practicum procedures. AR technology can be used to visualize tutorial videos that can be accessed offline.